Pengaruh Fraud Triangle dan Stabilitas Keuangan Terhadap Kecurangan Laporan Keuangan - Daffa Syafiq Khairullah; Rusdi Rusdi (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Financial statement fraud remains a critical issue that undermines the credibility of financial reporting and investor confidence, particularly in capital-intensive sectors such as infrastructure. This study aims to examine the effect of Pressure, Opportunity, Rationalization, and Financial Stability on Financial Statement Fraud in infrastructure sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach with an associative research design. Panel data regression analysis is used to test the proposed hypotheses. The sample consists of 26 companies selected through purposive sampling, resulting in 130 firm-year observations. The data were obtained from audited financial statements and annual reports published by the companies, and the analysis was conducted using EViews 12. The empirical results indicate that Pressure has a significant partial effect on Financial Statement Fraud, while Opportunity, Rationalization, and Financial Stability do not show a significant individual effect. However, simultaneously, Pressure, Opportunity, Rationalization, and Financial Stability have a significant influence on Financial Statement Fraud. These findings suggest that managerial pressure plays a dominant role in encouraging fraudulent financial reporting, although fraud risk is better understood when considering the interaction of multiple factors. The study implies that fraud prevention efforts should prioritize managing financial and performance pressures while also strengthening internal controls and governance mechanisms.